2020
DOI: 10.1007/s15010-020-01411-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance and impact of Corynebacterium isolation in lower respiratory tract of critically ill patients requiring mechanical ventilation

Abstract: Purpose Corynebacterium spp. (C. spp.) is commonly considered as a contaminant in respiratory specimens. No study has ever focused on its clinical relevance in the lower respiratory tract of patients admitted to the intensive care unit (ICU) and requiring mechanical ventilation. The aims were to describe the characteristics of ICU patients with a C. spp. positive deep respiratory specimen, to investigate the impact of C. spp. on the occurrence of pneumonia, and to evaluate the outcomes of these pneumonia. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Based on such studies, Clariot et al suggested that Corynebacterium spp. may be responsible for pneumonia in mechanically ventilated patients, similar to our results [ 33 ], while Yasuda et al reported that C. ulcerans produces diphtheria toxin and causes severe pneumonia complicated by diffuse pseudomembrane formation in the central airways [ 36 ]. Corynebacterium spp.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Based on such studies, Clariot et al suggested that Corynebacterium spp. may be responsible for pneumonia in mechanically ventilated patients, similar to our results [ 33 ], while Yasuda et al reported that C. ulcerans produces diphtheria toxin and causes severe pneumonia complicated by diffuse pseudomembrane formation in the central airways [ 36 ]. Corynebacterium spp.…”
Section: Discussionsupporting
confidence: 90%
“…are among the commensal flora of the nasopharynx [32], a causative role in pneumonia was recently described [33][34][35][36]. The identification of Corynebacteria subspecies is now possible using new diagnostic technologies, such as matrix-assisted laser desorption ionization time of flight mass spectrometry and 16S rRNA gene sequencing [13,[33][34][35]37]. Based on such studies, Clariot et al suggested that Corynebacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired airway protection, decreased lung clearance, damaged lung structure, antibiotic exposure, primary immunocompromised conditions or acquired im-munodeficiency after a prolonged stay in ICU were all conditions that can be encountered in ICU, and that may promote the onset of pneumonia caused by Corynebacterium spp. 33 Nowadays, the risk of pneumonia is increased in the intubated patients receiving mechanical ventilation and the ventilator associated pneumonia nosocomial pneumonia due to mechanical ventilation procedures in mechanically ventilated patients is a matter of concern world wild, including Brazil. 34 Remarkably, current findings also indicated ventilator support as a risk factor for acquiring C. striatum infection.…”
Section: Discussionmentioning
confidence: 99%
“…are among the commensal ora of the nasopharynx [32], a causative role in pneumonia was recently described [33][34][35][36]. The identi cation of Corynebacteria subspecies is now possible using new diagnostic technologies, such as matrix-assisted laser desorption ionization time of ight mass spectrometry and 16S rRNA gene sequencing [13,[33][34][35]37]. Based on such studies, Clariot et al suggested that Corynebacterium spp.…”
Section: Discussionmentioning
confidence: 99%